Feature Selection and Ranking Method based on Intuitionistic Fuzzy Matrix and Rough Sets - Vo, Bich Khue; Son Nguyen, Hung (2022 17th Conference on Computer Science and Intelligence Systems (FedCSIS), 2022)
In this paper we propose a novel rough-fuzzy hybridization technique to feature selection and feature ranking problem. The idea is to model the local preference relation between pair of features by intuitionistic fuzzy values and search for a feature ranking that is consistent with those constraints. We apply the techniques used in group decision making where constraints are presented in form of intuitionistic fuzzy preference relation. The proposed method has been illustrated by some simple examples and verified on a benchmark dataset.